Mantoux’s Test and Diagnostic BCG for Diagnosis of Tuberculosis in Children - Fahad Nazir, Qiam Ud Din, Zubariah, Saba Afzal Shaikh, Ibrahim, Abid Rafiq Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of Mantoux’s test and diagnostic BCG test in the diagnosis of tuberculosis in children by taking AFB (acid fast bacilli) sputum test as gold standard. Study Design: Cross Sectional study. Setting: Imran Idrees Teaching Hospital Sialkot. Duration of Study: This study was conducted from 1st August 2021 to 31st August 2022. Subjects and methods: A total of 260 patients of both gender presented with history of cough, fever and weight loss with history of close contact with tuberculosis were included. Mantoux’s test and diagnostic bacilli calmette Guerin was applied simultaneously to all the subjects. Data regarding Mantoux’s test, diagnostic bacilli calmette Guerin and AFB (acid fast bacilli) sputum test was recorded. Results: Mantoux’s test diagnosed 10.4% patients, Diagnostic BCG test 13.8% and AFB diagnosed 16.9% patients with Tuberculosis. Mantoux’s test has shown sensitivity of 29.54%, specificity 93.5%, diagnostic accuracy by 83%, PPV 48.1%, NPV 86.7% in diagnosis of Tuberculosis. Diagnostic BCG test has shown sensitivity of 59.09%, specificity 95.4%, diagnostic accuracy by 89%, PPV 72.2%, NPV 91.9% in diagnosis of Tuberculosis. Conclusion: BCG test is more sensitive than the Mantoux’s test but the specificity of Mantoux’s test was equal to the BCG test. Keywords: Tuberculosis, Mantoux’s test, Diagnostic BCG, Diagnostic accuracy